2018
DOI: 10.3389/fpls.2018.00428
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seaweed Extracts From Laminaria and Ascophyllum nodosum spp. as Biostimulants in Zea mays L. Using a Combination of Chemical, Biochemical and Morphological Approaches

Abstract: Seaweed extracts can be employed as biostimulants during crop cultivation owing to their positive effects on plant performance. Therefore, in this study one extract from Laminaria (A) and five extracts from Ascophyllum nodosum (B–F) were assayed on maize (Zea mays L.) plants supplied for 2 days with 0.5 mL L−1 of single products to evaluate their capacity to stimulate root growth and morphology, nutrition, and sugars accumulation. Firstly, extracts were chemically characterized via Fourier transform infrared (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 55 publications
5
83
0
5
Order By: Relevance
“…2a). Previous studies have shown that algal extracts and their purified compounds can induce strong physiological responses in plants and increase shoot and/or root weight 5,[16][17][18][19][20] . In addition, microalgae extracts such as polysaccharides have proven to enhance growth of agricultural crops 13,15,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…2a). Previous studies have shown that algal extracts and their purified compounds can induce strong physiological responses in plants and increase shoot and/or root weight 5,[16][17][18][19][20] . In addition, microalgae extracts such as polysaccharides have proven to enhance growth of agricultural crops 13,15,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, extract obtained through water or acid hydrolysis are reported to be rich in phytohormones [18], although such trait may also be inconsistent. Indeed, the previous findings of Ertani et al [19] revealed notable variation of indole acetic acid (IAA) and gibberellic acid (GA) content of five commercial Ascophyllum nodosum-based biostimulants produced via acid extraction, which was plausibly attributed to differences in the sampling zone, timing, and environmental conditions. At the industrial level, the most widely used extraction process implies heating the algae biomass with potassium hydroxide or sodium solvents in pressurized reaction vessels [9].…”
Section: Manufacturing Process Of Seaweed Extract Biostimulant: the Mmentioning
confidence: 97%
“…Both research groups attributed the higher plant productivity to the major components of commercial seaweed extracts (30-40% of the extract on dry weight basis), such as polysaccharides (alginates, fucoidan and laminarins), which are well known for triggering endogenous hormone homeostasis [35,36].…”
Section: Experimental Design Plant Biostimulants Application and Culmentioning
confidence: 99%